Analisis Pemanfaatan Financial Teknologi (BTN Mobile) Pada Bank BTN Syariah (Bank BTN KC Syariah Medan) - Agung Nugraha (Journal of Islamic Economics and Finance, 2024)
This research aims to determine the benefits of applying financial technology to the use of BTN Syariah mobile banking for BTN Syariah customers. It is known that BTN Syariah e-banking plays an important role in making it easier for customers to carry out transactions quickly and efficiently without having to go directly to the bank, just using a smartphone, customers can carry out transactions in banking. This writing uses a descriptive qualitative method which aims to explain and describe clearly and in detail the existence of a problem that occurred. The writing method for this article also uses library research or literature research which takes sources or references through previous journal articles and also sources from the internet.